A CsPbBr 3 / TiO 2 Composite material and its preparation method and application
By using the combination of solitary-gel method and water-heat-burning in the photocatalyst, prepare CSPBBR3/TIO2 composite materials with a horchogenic structure, solve the problem of low efficiency of existing photocatalysts in toluene oxidation reactions, and achieve efficient efficiency , Selective visible optical oxidation effect, reducing energy consumption and increasing the added value of the product.
Patent Information
- Application Number
- CN202211447859.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-18
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2042-11-18
AI Technical Summary
In the toluene oxidation reaction, existing photocatalysts have problems such as low solar energy utilization rate, high photocarrier recombination rate, and low product selectivity. In addition, traditional catalysts need to activate toluene, which leads to high cost and high energy consumption and has negative impact on the environment. .
The method of combining the solution-gel method and water thermal-burn is used to prepare a two-dimensional TIO2 nanometer with a grade porous structure, and the CSPBBR3 nano particles with TIO2 nano-slices are used to form a good interface contact through the anti-solvent method to build CSPBBBR3/TIO2/TIO2 Composite materials.
The optical catalytic performance is improved, and the high -efficiency selective oxide and derivatives can be used at visible light. The selectivity of the aldehyde products is more than 75%, reducing energy consumption and increasing the added value of the product.
Smart Images

Figure CN115739135B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of catalyst preparation and sustainable development of environment and energy, and specifically relates to a CsPbBr3 / TiO2 composite material and a preparation method and application thereof. Background Art
[0002] Direct oxidation of toluene to produce high value-added fine chemicals such as alcohols and aldehydes is one of the most important transformations in the chemical industry. 3 )-H bond inertness and high dissociation energy (89.8 kcal mol -1 ), the activation of toluene usually needs to be carried out under high temperature and high pressure, and requires the use of specific metal complex catalysts or corrosive oxidants, which leads to high cost and high energy consumption, and also has a significant negative impact on the environment. The photocatalytic selective oxidation reaction system is usually carried out under simple and mild conditions, which solves the difficulties faced in traditional organic synthesis. However, the current photocatalysts generally have problems such as low solar energy utilization, high recombination rate of photogenerated carriers, and low product selectivity.
[0003] In recent years, halide perovskite materials have attracted extensive attention in the field of photocatalysis due to their excellent optical and electronic properties. However, single-component halide perovskites usually exist in bulk structures with large particles (size ranging from a few microns to tens of microns), which leads to serious carrier bulk recombination and reduces the photocatalytic performance. Constructing a heterojunction structure is an effective way to solve the above problems. It can not only prevent the aggregation of halide perovskites and reduce the bulk recombination of photogenerated electron-hole pairs, but also establish a built-in electric field at the interface, further promoting spatial charge transfer and separation.
[0004] As a non-toxic, biocompatible and highly stable oxide semiconductor photocatalytic material, TiO2 has been widely used in the fields of environmental pollutant degradation, photolysis of water to produce hydrogen, etc. However, since TiO2 is a wide bandgap semiconductor, it requires ultraviolet light for excitation and can only use a narrow wavelength range of sunlight, making it difficult to be a visible light responsive photocatalyst.
[0005] In addition, in order to obtain high photocatalytic performance, designing and constructing heterojunction composite materials with fine nanostructures is also an important factor. For different spatial configurations, the three-dimensional hierarchical nanostructure constructed by two-dimensional nanosheets has obvious advantages in photocatalysis. It can not only enhance the utilization of light, but also prevent the aggregation of nanosheets and maintain the structural advantages of two-dimensional materials, thereby effectively improving the photocatalytic efficiency. Therefore, the development of heterojunctions with hierarchical structures assembled by two-dimensional nanosheets is of great significance for the efficient photocatalytic oxidation of toluene.
[0006] The patent with publication number CN110975894A is "A visible light responsive, efficient and stable nano CsPbBr 3 / The invention discloses a composite photocatalyst of amorphous TiO2 coated with nano-CsPbBr3, which is prepared by combining the strong absorption performance of CsPbBr3 in a wide wavelength range with the high stability of TiO2. However, the invention only adopts a simple liquid phase method to combine the two, and does not involve high-temperature heat treatment, so that a good interface contact cannot be formed between CsPbBr3 and TiO2. The patent with publication number CN110813331A, "A BiOBr / TiO2 composite photocatalyst and its preparation method", uses BiOBr and TiO2 photocatalysts to prepare photocatalysts with high activity and universality under visible light. However, the TBOT used in the preparation process of the invention has a hygroscopic property and has a very high chemical activity to water. It can quickly absorb moisture in the air and decompose, and hydrolyze to generate Ti(OH)4, so it must be stored in a water-free environment, and the straws used in the preparation process must be cleaned in time. Summary of the invention
[0007] The present invention introduces a CsPbBr3 / TiO2 composite material and a preparation method and application thereof. The present invention prepares a two-dimensional TiO2 nanosheet with a hierarchical porous structure by combining a sol-gel method with a hydrothermal-calcination method, then adds a precursor organic solution containing Cs, Pb and Br ions into the TiO2 nanosheet dispersion, and obtains the CsPbBr3 / TiO2 composite material with a hierarchical porous structure by an anti-solvent method.
[0008] The technical solution of the present invention is as follows:
[0009] One of the purposes of the present invention is to provide a CsPbBr3 / TiO2 composite material, wherein the CsPbBr3 / TiO2 composite material has a hierarchical porous sheet structure, the loaded CsPbBr3 nanoparticles are small in size and have good interface contact with the two-dimensional TiO2 nanosheets; wherein the mass percentage of CsPbBr3 is 10%-40%.
[0010] The second object of the present invention is to provide a method for preparing a CsPbBr3 / TiO2 composite material, which comprises preparing a two-dimensional TiO2 nanosheet having a hierarchical porous structure by combining a sol-gel method with a hydrothermal-calcination method, and then adding a precursor organic solution containing Cs, Pb and Br ions to the TiO2 nanosheet dispersion to obtain a CsPbBr3 / TiO2 composite material having a hierarchical porous structure by an anti-solvent method.
[0011] Furthermore, the preparation method is as follows:
[0012] S1. Add polyether F127 to a mixed solution of tetrahydrofuran and glacial acetic acid, add concentrated hydrochloric acid dropwise while stirring, and then add tetrabutyl titanate dropwise to the mixed solution after vigorous stirring. After continuing to stir, add distilled water dropwise to obtain an orange-red solution, and place the obtained solution in an oven to dry to obtain a light yellow gel;
[0013] S2, adding the light yellow gel into the glycerol / ethanol solvent and stirring, then transferring it to the lining of the hydrothermal kettle for hydrothermal treatment, cooling it naturally at room temperature after the hydrothermal treatment, filtering, washing and drying the white precipitate;
[0014] S3, calcining the white precipitate in a muffle furnace, and then grinding it evenly, and the resulting white powder is a two-dimensional TiO2 nanosheet with a hierarchical porous structure;
[0015] S4. Drop the solution containing CsBr and PbBr2 into the two-dimensional TiO2 nanosheet dispersion under vigorous stirring, pour it into the toluene solution after stirring, continue to stir and then centrifuge, and put the collected solid into a vacuum oven to dry, so as to obtain a CsPbBr3 / TiO2 composite material.
[0016] Furthermore, in the S1, the mass of the polyether F127 is 1.0-2.0 g, the volume of tetrahydrofuran is 25-40 mL, the volume of glacial acetic acid is 2.0-3.0 mL, the volume of concentrated hydrochloric acid is 3.0-4.0 mL, the volume of tetrabutyl titanate is 3.0-4.0 mL, and the volume of distilled water is 0.15-0.25 mL.
[0017] Furthermore, in S1, the oven temperature is 40-50° C., and the drying time is 24-36 hours.
[0018] Furthermore, the mass of the light yellow gel in S2 is 1.0-2.0 g, the volume of the glycerol / ethanol solvent is 30 mL, wherein the volume of glycerol to ethanol is 1:5-1:1, the hydrothermal treatment temperature is 120-150° C., and the hydrothermal treatment time is 12-15 h.
[0019] Furthermore, the calcination temperature of the muffle furnace in S3 is 400° C.-500° C., and the calcination time is 8-10 hours.
[0020] Furthermore, the solvent of the CsBr and PbBr2 solutions in S4 is DMF, the TiO2 dispersion is a mixed solution of TiO2 nanosheets dispersed in DMF, and the volume ratio of toluene to DMF is 4:1-7:1.
[0021] Furthermore, the speed of the vigorous stirring in S4 is 1000-2000 rpm, the centrifugal speed is 8000 rpm, and the centrifugal time is 5 min.
[0022] The third object of the present invention is to provide an application of a CsPbBr3 / TiO2 composite material, wherein the CsPbBr3 / TiO2 composite material has excellent photocatalytic performance and is used for photocatalytic selective oxidation of toluene and its derivatives to corresponding aldehydes under visible light.
[0023] Compared with the prior art, the beneficial effects of the present invention are:
[0024] 1. The CsPbBr3 / TiO2 composite material prepared by the present invention has a hierarchical porous sheet structure. The loaded CsPbBr3 nanoparticles have a small size and form a good interface contact with the hierarchical porous TiO2 nanosheets, which can form a tight heterojunction and effectively improve the photocatalytic performance.
[0025] 2. The CsPbBr3 / TiO2 composite material prepared by the present invention has high catalytic activity and can selectively oxidize toluene and its derivatives to corresponding aldehydes by photocatalysis with visible light as driving energy and oxygen as oxidant. After irradiation with visible light with a wavelength greater than 420 nm for 2 h, the oxidation rate of toluene and its derivatives is 5950-12746 μmol g -1 h -1 Except for m-xylene and p-xylene (71%), the selectivity of the corresponding product aldehydes is more than 75%, which is of great significance in the practical application of selective oxidation of toluene and its derivatives, and is beneficial to the sustainable development of the environment and energy.
[0026] 3. In the present invention, CsPbBr3 with strong absorption performance of visible light in a wide wavelength range is combined with TiO2 with high stability to prepare an efficient and stable nano CsPbBr3 / TiO2 composite photocatalyst. The preparation process is simple and the manufacturing cost is low. It operates in a natural air atmosphere and does not require inert gas protection measures, which can meet the requirements of large-scale industrial production.
[0027] Reference numerals
[0028] Figure 1 XRD diagrams of CsPbB3 / TiO2 composite materials with different proportions and blank CsPbBr3 and TiO2 in the present invention;
[0029] Figure 2 The SEM images of CsPbB3 / TiO2 composite materials with different ratios and blank CsPbBr3 photocatalysts in the present invention;
[0030] Figure 3 is the SEM image of blank CsPbBr3 photocatalyst;
[0031] Figure 4TEM image of 20% CsPbB3 / TiO2 photocatalyst in the present invention;
[0032] Figure 5 Columnar activity diagram of selective oxidation of toluene to benzaldehyde and benzyl alcohol by CsPbB3 / TiO2 composite materials with different ratios in the present invention;
[0033] Figure 6 This is a columnar activity diagram of the selective oxidation of toluene and its derivatives to corresponding aldehydes and alcohols by 20% CsPbB3 / TiO2 photocatalyst in the present invention. DETAILED DESCRIPTION
[0034] The present invention will be further described below in conjunction with the accompanying drawings and preferred embodiments. The given embodiments are only for illustrating the present invention, rather than for limiting the scope of the present invention.
[0035] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources;
[0036] The quantitative tests in the following examples were repeated three times, and the results were averaged.
[0037] The experimental methods in the following embodiments are conventional methods unless otherwise specified.
[0038] Example 1 Preparation of 10% CsPbBr3 / TiO2 Composite Material
[0039] This embodiment provides a CsPbBr3 / TiO2 composite material, which specifically includes the following steps:
[0040] S1. Add 1.0 g of polyether F127 to 25 mL of a mixed solution consisting of tetrahydrofuran and 2.0 mL of glacial acetic acid, add 3.0 mL of concentrated hydrochloric acid dropwise while stirring, stir vigorously for 10 min, then add 3.0 mL of tetrabutyl titanate dropwise to the mixed solution, continue stirring for 10 min, then add 0.15 mL of distilled water dropwise to obtain an orange-red solution, and place the obtained solution in a 40°C oven to dry for 24 h to obtain a light yellow gel;
[0041] S2, add 1.0g of light yellow gel into 30mL of glycerol / ethanol solvent and stir for 20min, the volume ratio of glycerol to ethanol is 1:5, then transfer to the lining of hydrothermal kettle for hydrothermal treatment at 120℃ for 12h, cool naturally at room temperature after the hydrothermal treatment, filter, wash and dry the white precipitate;
[0042] S3, calcining the white precipitate at 400°C in a muffle furnace for 8 h, and then grinding it evenly. The resulting white powder is a two-dimensional TiO2 nanosheet with a hierarchical porous structure;
[0043] S4, weigh 106 mg CsBr and 183.5 mg PbB2, dissolve them in 12 mL DMF to obtain CsBr and PbBr2 solutions, weigh 200 mg two-dimensional TiO2 nanosheets and disperse them in 12 mL DMF to obtain TiO2 white dispersion;
[0044] S5. Under vigorous stirring, a solution containing 0.9 mL of CsBr and PbBr2 was dropped into the dispersion of TiO2 prepared above at a speed of 1000 rpm. After stirring for 10 minutes, the mixed solution was quickly poured into the toluene solution and continued to be stirred for 30 minutes. After stirring, it was centrifuged at 8000 rpm for 5 minutes, and the collected solid was placed in a vacuum oven for drying to obtain a 10% CsPbBr3 / TiO2 composite material, named 10% CPB / TiO2.
[0045] Example 2 Preparation of 20% CsPbBr3 / TiO2 Composite Material
[0046] This embodiment provides a method for preparing a CsPbBr3 / TiO2 composite material, which specifically includes the following steps:
[0047] S1. Add 1.5 g of polyether F127 to 30 mL of a mixed solution consisting of tetrahydrofuran and 2.4 mL of glacial acetic acid, add 3.2 mL of concentrated hydrochloric acid dropwise while stirring, stir vigorously for 15 min, then add 3.0 mL of tetrabutyl titanate dropwise to the mixed solution, continue stirring for 15 min, then add 0.2 mL of distilled water dropwise to obtain an orange-red solution, and place the obtained solution in a 42°C oven to dry for 26 h to obtain a light yellow gel;
[0048] S2, add 1.0 g of light yellow gel into 30 mL of glycerol / ethanol solvent and stir for 30 min, the volume ratio of glycerol to ethanol is 1:5, then transfer to the lining of the hydrothermal kettle for hydrothermal treatment at 150° C. for 15 h, cool naturally at room temperature after the hydrothermal treatment, filter, wash and dry the white precipitate;
[0049] S3, calcining the white precipitate at 400°C in a muffle furnace for 8 h, and then grinding it evenly. The resulting white powder is a two-dimensional TiO2 nanosheet with a hierarchical porous structure;
[0050] S4, weigh 106 mg CsBr and 183.5 mg PbB2, dissolve them in 12 mL DMF to obtain CsBr and PbBr2 solutions, weigh 200 mg two-dimensional TiO2 nanosheets and disperse them in 12 mL DMF to obtain TiO2 white dispersion;
[0051] S5. Under vigorous stirring, a solution containing 2.1 mL of CsBr and PbBr2 was dropped into the dispersion of TiO2 prepared above at a speed of 1300 rpm. After stirring for 15 min, the mixed solution was quickly poured into the toluene solution and continued to be stirred for 40 min. After stirring, the mixture was centrifuged at 8000 rpm for 5 min, and the collected solid was placed in a vacuum oven and dried to obtain a 20% CsPbBr3 / TiO2 composite material, named 20% CPB / TiO2.
[0052] Example 3 Preparation of 30% CsPbBr3 / TiO2 Composite Material
[0053] This embodiment provides a method for preparing a CsPbBr3 / TiO2 composite material, which specifically includes the following steps:
[0054] S1. Add 1.5 g of polyether F127 to 30 mL of a mixed solution consisting of tetrahydrofuran and 2.4 mL of glacial acetic acid, add 3.2 mL of concentrated hydrochloric acid dropwise while stirring, stir vigorously for 15 min, then add 3.0 mL of tetrabutyl titanate dropwise to the mixed solution, continue stirring for 15 min, then add 0.2 mL of distilled water dropwise to obtain an orange-red solution, and place the obtained solution in a 42°C oven to dry for 26 h to obtain a light yellow gel;
[0055] S2, add 1.5g of light yellow gel into 30mL of glycerol / ethanol solvent and stir for 30min, the volume ratio of glycerol to ethanol is 1:3, then transfer to the lining of hydrothermal kettle for hydrothermal treatment at 130℃ for 14h, cool naturally at room temperature after the hydrothermal treatment, filter, wash and dry the white precipitate;
[0056] S3, calcining the white precipitate at 450°C in a muffle furnace for 9 hours, and then grinding it evenly. The obtained white powder is a two-dimensional TiO2 nanosheet with a hierarchical porous structure;
[0057] S4, weigh 106 mg CsBr and 183.5 mg PbB2, dissolve them in 12 mL DMF to obtain CsBr and PbBr2 solutions, weigh 200 mg two-dimensional TiO2 nanosheets and disperse them in 12 mL DMF to obtain TiO2 white dispersion;
[0058] S5. Under vigorous stirring, a solution containing 3.6 mL of CsBr and PbBr2 was dropped into the dispersion of TiO2 prepared above at a speed of 1500 rpm. After stirring for 20 min, the mixed solution was quickly poured into the toluene solution and continued to be stirred for 35 min. After stirring, it was centrifuged at 8000 rpm for 5 min, and the collected solid was placed in a vacuum oven for drying to obtain a 30% CsPbBr3 / TiO2 composite material, named 30% CPB / TiO2.
[0059] Example 4 Preparation of 40% CsPbBr3 / TiO2 Composite Material
[0060] This embodiment provides a method for preparing a CsPbBr3 / TiO2 composite material, which specifically includes the following steps:
[0061] S1. Add 2.0 g of polyether F127 to 40 mL of a mixed solution consisting of tetrahydrofuran and 3.0 mL of glacial acetic acid, add 4.0 mL of concentrated hydrochloric acid dropwise while stirring, stir vigorously for 20 min, then add 4.0 mL of tetrabutyl titanate dropwise to the mixed solution, continue stirring for 20 min, then add 0.25 mL of distilled water dropwise to obtain an orange-red solution, and place the obtained solution in a 50°C oven to dry for 36 h to obtain a light yellow gel;
[0062] S2, adding 2.0 g of light yellow gel into 30 mL of glycerol / ethanol solvent and stirring for 30 min, the volume ratio of glycerol to ethanol being 1:1, and then transferring to the inner lining of a hydrothermal kettle for hydrothermal treatment at 150° C. for 15 h, cooling naturally at room temperature after the hydrothermal treatment, filtering, washing and drying the white precipitate;
[0063] S3, calcining the white precipitate at 500°C in a muffle furnace for 10 h, and then grinding it evenly. The resulting white powder is a two-dimensional TiO2 nanosheet with a hierarchical porous structure;
[0064] S4, weigh 106 mg CsBr and 183.5 mg PbB2, dissolve them in 12 mL DMF to obtain CsBr and PbBr2 solutions, weigh 200 mg two-dimensional TiO2 nanosheets and disperse them in 12 mL DMF to obtain TiO2 white dispersion;
[0065] S5. Under vigorous stirring, a solution containing 5.5 mL of CsBr and PbBr2 was dropped into the dispersion of TiO2 prepared above at a speed of 2000 rpm. After stirring for 30 minutes, the mixed solution was quickly poured into a toluene solution and continued to be stirred for 60 minutes. After stirring, the mixture was centrifuged at 8000 rpm for 5 minutes, and the collected solid was placed in a vacuum oven for drying to obtain a 40% CsPbBr3 / TiO2 composite material, named 40% CPB / TiO2.
[0066] Figure 1 The XRD patterns of different samples show that all catalysts have good crystal structures, and as the ratio of CsPbBr3 increases, the perovskite diffraction peak gradually increases, indicating that CsPbBr3 / TiO2 photocatalysts with different ratios have been successfully synthesized.
[0067] Figure 2The SEM images of CsPbBr3 / TiO2 photocatalysts with different ratios clearly show that with the increase of CsPbBr3 content, the size of CsPbBr3 particles begins to increase and gradually aggregates on the TiO2 nanosheets;
[0068] Figure 3 This is the SEM image of the blank CsPbBr3 photocatalyst. It can be clearly seen that the particle size of the blank CsPbBr3 is 0.9μm-2.1μm, which is much larger than the particle size of CsPbBr3 in the composite material.
[0069] Figure 4 This is the TEM image of the 20% CsPbBr3 / TiO2 catalyst. In the image, characteristic crystal plane stripes representing CsPbBr3 and TiO2 can be seen; in addition, Cs, Pb, Br, Ti, and O elements are evenly distributed on the nanosheet structure, all of which indicate that good interface contact is formed between CsPbBr3 and TiO2.
[0070] Example 5 Photocatalytic Selective Oxidation of Toluene by CsPbBr3 / TiO2
[0071] This embodiment provides an application of a CsPbBr3 / TiO2 composite material, which specifically includes the following steps:
[0072] First, 2 mL of acetonitrile, 1 mL of toluene and 10 mg of catalyst were placed in a 25 mL quartz reaction bottle, stirred evenly, illuminated with visible light for 2 h, and centrifuged to obtain the supernatant;
[0073] Then, the supernatant in S1 was analyzed by gas chromatography, and the product was qualitatively and quantitatively analyzed by retention time and peak area to obtain the product generation rate.
[0074] like Figure 5 As shown in Figure 2, the toluene oxidation rate reaches a maximum value (10200 μmol g) when the perovskite content is 20%. -1 h -1 ), the benzaldehyde generation rate is 8670 μmol g -1 h -1 , the selectivity reaches 85%.
[0075] Example 6 CsPbBr3 / TiO2 Photocatalytic Selective Oxidation of a Series of Toluene Derivatives
[0076] This embodiment provides an application of a CsPbBr3 / TiO2 composite material, which specifically includes the following steps:
[0077] First, 2 mL of acetonitrile, 1 mL of toluene derivative and 10 mg of 20% CsPbBr3 / TiO2 composite material were placed in a 25 mL quartz reaction bottle, stirred evenly, illuminated with visible light for 2 h, and centrifuged to obtain the supernatant;
[0078] Then, the supernatant in S1 was analyzed by gas chromatography, and the product was qualitatively and quantitatively analyzed by retention time and peak area to obtain the product generation rate.
[0079] like Figure 6 As shown, the oxidation rate of p-fluorotoluene is 5950 μmol g -1 h -1 The oxidation rate of p-chlorotoluene is 9040 μmol g -1 h -1 The oxidation rate of p-bromotoluene is 9770 μmol g -1 h -1 , the oxidation rate of o-xylene is 9900 μmol g - 1 h -1 The oxidation rate of m-xylene is 10930 μmol g -1 h -1 The oxidation rate of p-xylene is 12746 μmol g -1 h -1 Except for m-xylene and p-xylene (71%), the selectivity of the corresponding product aldehydes is above 75%.
[0080] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A method for preparing a CsPbBr3 / TiO2 composite material, characterized in that: The CsPbBr3 / TiO2 composite material has a hierarchical porous sheet structure, and the loaded CsPbBr3 nanoparticles are small in size and have good interface contact with the two-dimensional TiO2 nanosheets; wherein the mass percentage of CsPbBr3 is 10%-40%; The preparation method of the CsPbBr3 / TiO2 composite material is as follows: a two-dimensional TiO2 nanosheet having a hierarchical porous structure is prepared by combining a sol-gel method with a hydrothermal-calcination method, and then a precursor organic solution containing Cs, Pb and Br ions is added to the two-dimensional TiO2 nanosheet dispersion, and a CsPbBr3 / TiO2 composite material having a hierarchical porous structure is obtained by an anti-solvent method; The specific steps include: S1. Add polyether F127 to a mixed solution of tetrahydrofuran and glacial acetic acid, add concentrated hydrochloric acid dropwise while stirring, and then add tetrabutyl titanate dropwise to the mixed solution after vigorous stirring. After continuing to stir, add distilled water dropwise to obtain an orange-red solution, and place the obtained solution in an oven to dry to obtain a light yellow gel; S2, adding the light yellow gel into the glycerol / ethanol solvent and stirring, then transferring it to the lining of the hydrothermal kettle for hydrothermal treatment, cooling it naturally at room temperature after the hydrothermal treatment, filtering, washing and drying the white precipitate; S3, calcining the white precipitate in a muffle furnace, and then grinding it evenly, and the resulting white powder is a two-dimensional TiO2 nanosheet with a hierarchical porous structure; S4. Drop the solution containing CsBr and PbBr2 into the two-dimensional TiO2 nanosheet dispersion under vigorous stirring, pour it into the toluene solution after stirring, continue to stir and then centrifuge, and put the collected solid into a vacuum oven to dry, so as to obtain a CsPbBr3 / TiO2 composite material.
2. The method for preparing a CsPbBr3 / TiO2 composite material according to claim 1, characterized in that: The mass of polyether F127 in S1 is 1.0-2.0 g, the volume of tetrahydrofuran is 25-40 mL, the volume of glacial acetic acid is 2.0-3.0 mL, the volume of concentrated hydrochloric acid is 3.0-4.0 mL, the volume of tetrabutyl titanate is 3.0-4.0 mL, and the volume of distilled water is 0.15-0.25 mL.
3. The method for preparing a CsPbBr3 / TiO2 composite material according to claim 1, characterized in that: In S1, the oven temperature is 40-50° C. and the drying time is 24-36 hours.
4. The method for preparing a CsPbBr3 / TiO2 composite material according to claim 1, characterized in that: The mass of the light yellow gel in S2 is 1.0-2.0 g, the volume of the glycerol / ethanol solvent is 30 mL, wherein the volume of glycerol to ethanol is 1:5-1:1, the hydrothermal treatment temperature is 120-150° C., and the hydrothermal treatment time is 12-15 h.
5. The method for preparing a CsPbBr3 / TiO2 composite material according to claim 1, characterized in that: The muffle furnace calcination temperature in S3 is 400° C.-500° C., and the calcination time is 8-10 hours.
6. The method for preparing a CsPbBr3 / TiO2 composite material according to claim 1, characterized in that: The solvent of the CsBr and PbBr2 solutions in S4 is DMF, the TiO2 dispersion is a mixed solution of TiO2 nanosheets dispersed in DMF, and the volume ratio of toluene to DMF is 4:1-7:
1.
7. The method for preparing a CsPbBr3 / TiO2 composite material according to claim 1, characterized in that: The speed of the vigorous stirring in S4 is 1000-2000 rpm, the centrifugal speed is 8000 rpm, and the centrifugal time is 5 min.
8. An application of the CsPbBr3 / TiO2 composite material obtained by the method of claim 1, characterized in that: The CsPbBr3 / TiO2 composite material has excellent photocatalytic performance and is used for photocatalytic selective oxidation of toluene and its derivatives to corresponding aldehydes under visible light.
Citation Information
Patent Citations
BiOBr / TiO2 composite photocatalyst and preparation method thereof
CN110813331A
Visible light response type efficient and stable nano-CsPbBr3 / TiO2 composite photocatalyst and preparation method thereof
CN110975894A
Preparation method of two-dimensional porous titanium dioxide nano sheet
CN112516980A